2021
DOI: 10.20515/otd.907362
|View full text |Cite
|
Sign up to set email alerts
|

Bir Tıp Fakültesi Öğrencilerinin COVID-19 Hastalığı ile İlgili Bilgi Düzeylerinin ve Davranışlarının Değerlendirilmesi

Abstract: Tıp fakültesi öğrencilerinin COVID-19 hastalığı ile ilgili bilgi düzeylerinin saptanması, ilişkili olduğu düşünülen bazı değişkenlerin incelenmesi ve COVID-19 hastalığı ile ilgili davranışlarının değerlendirilmesi amaçlanmıştır. 01.08.2020-30.10.2020 tarihleri arasında Eskişehir Osmangazi Üniversitesi Tıp Fakültesi öğrencileri üzerinde yapılan kesitsel tipte bir araştırmadır. 984 öğrenci çalışma grubunu oluşturdu. Yazarlar tarafından hazırlanan 26 soru ile öğrencilerin COVID-19 hastalığı ile ilgili bilgileri, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(1 reference statement)
1
1
0
Order By: Relevance
“…al. stated that social media ranked first with 74.6% in accessing information about COVID-19, similar to our findings, whereas Gölbaşı et al stressed that the most used source of information was international/national health authorities with 34.5%(29). The study carried out by Taghrir et al on medical faculty students reported that sources such as the World Health Organization (WHO), CDC, and UpToDate were used the most in accessing information about COVID-19 with 17.1%(22).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…al. stated that social media ranked first with 74.6% in accessing information about COVID-19, similar to our findings, whereas Gölbaşı et al stressed that the most used source of information was international/national health authorities with 34.5%(29). The study carried out by Taghrir et al on medical faculty students reported that sources such as the World Health Organization (WHO), CDC, and UpToDate were used the most in accessing information about COVID-19 with 17.1%(22).…”
supporting
confidence: 90%
“…In similar studies performed with medical faculty students in our country, Çalışkan et reported a weak positive correlation between the scores from the knowledge questions about COVID-19 disease and the scores from the behavioral questions (29). In their study, Pirincci et al emphasized that positive hygiene behaviors increased with the increasing knowledge score (18).…”
Section: Discussionmentioning
confidence: 78%